Corruption Prevention Strategy in Indonesia through Strengthening Character Education of Pancasila Ethics - Ruhadi, Ruhadi; Uddin, Hafiz Rafi (Semarang State University Undergraduate Law and Society Review, 2025)
Corruption has become a deeply rooted problem in Indonesia's governance system and society. Various efforts to eradicate corruption through legal and institutional approaches have not shown maximum results. This research aims to analyze corruption prevention strategies through strengthening character education as a more effective and sustainable alternative solution. Through a qualitative approach with literature study, this research examines the role of character education in forming generations with integrity and anti-corruption character. The results show that character education integrated into formal and non-formal educational curricula can be a strong foundation in preventing corrupt behavior from an early age. Strategies that can be applied include integrating anti-corruption values into the curriculum, strengthening the role of higher education, forming the character of generation Z, and implementing moral education as a preventive strategy. This research concludes that character education is a long-term investment capable of creating a clean and transparent culture in national and state life.